Applications of flow cytometry sorting in the pharmaceutical industry: A review. (4th April 2021) - Vitelli, Michael; Budman, Hector; Pritzker, Mark; Tamer, Melih
Abstract: The article reviews applications of flow cytometry sorting in manufacturing of pharmaceuticals. Flow cytometry sorting is an extremely powerful tool for monitoring, screening and separating single cells based on any property that can be measured by flow cytometry. Different applications of flow cytometry sorting are classified into groups and discussed in separate sections as follows: (a) isolation of cell types, (b) high throughput screening, (c) cell surface display, (d) droplet fluorescent‐activated cell sorting (FACS). Future opportunities are identified including: (a) sorting of particular fractions of the cell population based on a property of interest for generating inoculum that will result in improved outcomes of cell cultures and (b) the use of population balance models in combination with FACS to design and optimize cell cultures.